(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current study is to identify "the effect of using the Cabri3D program on geometric thinking of second intermediate students". The study sample consisted of (60) students from the second intermediate grade students in (Al-Amriya Intermediate School for Girls) affiliated to the General Directorate of Diyala Education for the academic year (2022-2023), and two divisions were chosen randomly to represent section (B) of the experimental group, with (30) students who It was taught according to the Cabri3D program, and section (D) to represent the control group of (30) students who were taught according to the traditional method, the two groups were rewarded in the variables (chronological age calculated in months, previous mathematical knowledge, intelligence, and engineering thinking, , and parents’ educational level). The study tools were prepared: the engineering thinking test according to the levels of (Van Hiele) theory, consisting of (20) items of multiple choice type with four alternatives and the validity of the test was verified and the stability coefficient were acceptable, as the Keuder-Richardson equation (KR-20) was used to find the stability of the test so the stability coefficient of the test items was (0.74), and after the end of the experiment the test was applied the data were processed statistically using the t-test for two independent samples, and the results were as follows: There is a statistically significant difference between the two groups (experimental and control) in the engineering thinking test in favor of the experimental group. In the light of the results of the study, the researcher recommended drawing the attention of staff members in the Department of Preparation and Training in the Ministry of Education to prepare training courses for teachers on how to use computerized electronic programs to teach mathematics, and to educate mathematics teachers and teachers of the need to adopt different methods in evaluation that focus on engineering thinking and benefit from the prepared engineering thinking test. In this study, it should be suggested to conducting a similar study in other variables: spatial thinking, reflective thinking, motivation towards geometry, and attitudes towards mathematics, and designing a proposed training program based on the Cabri3D program targeting teachers of mathematics